2016
DOI: 10.1111/1758-2229.12452
|View full text |Cite
|
Sign up to set email alerts
|

Yeasts from macroalgae and lichens that inhabit the South Shetland Islands, Antarctica

Abstract: Antarctic terrestrial ecosystems are largely dominated by lichens, while shallow coastal environments are mainly covered by macroalgae. The aim of this study was to isolate and to evaluate the diversity of yeasts in different species of macroalgae and lichens collected in South Shetland Islands, Antarctica. A total of 405 yeasts were recovered (205 from macroalgae and 200 from lichens). The yeast community from macroalgae was most diversity than the yeast community from lichen. The dominance index was similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 53 publications
1
23
0
4
Order By: Relevance
“…However, the closest BLAST-hits for lichenized fungi were described in several countries, primarily Sweden, United States and the United Kingdom. In contrast, 68% of the yeasts detected in this work were basidiomycetes, in agreement with our previous work on cultivable yeasts from these soils (74% corresponded to basidiomycetes) ( Carrasco et al, 2012 ; Contreras et al, 2015 ; Barahona et al, 2016 ; Troncoso et al, 2017 ) and other and other studies from Antarctic terrestrial habitats (84% basidiomycetes) ( Buzzini et al, 2012 ; Selbmann et al, 2014 ; Vasileva-Tonkova et al, 2014 ; Zhang et al, 2014 ; Duarte et al, 2016 ; Martinez et al, 2016 ). The predominance of the yeast phylum Basidiomycota has been attributed to their ability to produce polysaccharide capsules, utilize the available nutrients in oligotrophic systems and increase the proportion of unsaturated fatty acids ( Connell et al, 2008 ; Margesin and Miteva, 2011 ; Buzzini et al, 2012 ).…”
Section: Discussionsupporting
confidence: 93%
“…However, the closest BLAST-hits for lichenized fungi were described in several countries, primarily Sweden, United States and the United Kingdom. In contrast, 68% of the yeasts detected in this work were basidiomycetes, in agreement with our previous work on cultivable yeasts from these soils (74% corresponded to basidiomycetes) ( Carrasco et al, 2012 ; Contreras et al, 2015 ; Barahona et al, 2016 ; Troncoso et al, 2017 ) and other and other studies from Antarctic terrestrial habitats (84% basidiomycetes) ( Buzzini et al, 2012 ; Selbmann et al, 2014 ; Vasileva-Tonkova et al, 2014 ; Zhang et al, 2014 ; Duarte et al, 2016 ; Martinez et al, 2016 ). The predominance of the yeast phylum Basidiomycota has been attributed to their ability to produce polysaccharide capsules, utilize the available nutrients in oligotrophic systems and increase the proportion of unsaturated fatty acids ( Connell et al, 2008 ; Margesin and Miteva, 2011 ; Buzzini et al, 2012 ).…”
Section: Discussionsupporting
confidence: 93%
“…Debaryomyces hansenii is considered a cosmopolitan yeast species that is able to occupy and colonize different ecological niches and ecosystems. In Antarctica, D. hansenni was previously recovered from the rhizosphere of D. antarc tica and soil [48], as well as the soil and thalli of lichens [75], macroalgae [76], freshwater, and marine water [77]. However, D. hansenii (also reported as Candida famata , its anamorph) has been previously found to cause opportunistic human infections [78,79,80].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the number of papers published so far, the general knowledge on this issue still remains rather patchy since most of the studies were merely explorative or focused on the fungal diversity found in single Antarctic habitats (Connell et al ., 2006; Loque et al ., 2010; Duarte et al ., 2013, 2016; Vaca et al ., 2013; Borruso et al ., 2018; Coleine et al ., 2018a,b). Moreover, a complete investigation on the co‐occurrences of taxonomically‐related taxa sharing the same or different neighbouring habitats and an estimation of the putative interactions between chemical–physical (abiotic) parameters and fungal diversity have been rarely carried out (Hogg et al ., 2006; Arenz and Blanchette, 2011; Ferrari et al ., 2015; Newsham et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%